Toward becoming an inclusive library: Integrating Sustainable Development Goal 5 in the library agenda. Issue 2 (5th February 2020) - Yap, Joseph Marmol; Kamilova, Yelizaveta
Abstract : Purpose: The library's role in promoting and supporting the United Nations Agenda for Sustainable Development Goal (SDG) is beyond borders. It has the capacity to be a powerful driving force in leading exemplary programs that will transform society in many dimensions. This paper will share the value of libraries in integrating SDG's into their work and how it can positively advocate for change toward attaining an inclusive, open and tolerant society. Design/methodology/approach: This survey research and program evaluation are designed to solicit opinions from participants of two library programs focusing on gender equality at Nazarbayev University. Data collection was prepared, gathered and analyzed using Qualtrics. Findings: Participants believed that gender-related programs of the library are positive ways on how to stimulate a gender-balanced society. The programs increased awareness on gender equality among the academic community and promoted the welfare and rights of marginalized sectors. Finally, these programs addressed various stigmas, thus empowering vulnerable groups to stand up to discrimination. Practical implications: Libraries are safe spaces that advocate social inclusivity. Social implications: It proves that a library can hold programs in support of SDGs, particularly on gender equality. Originality/value: This paper shares academic library initiatives in Central Asia, particularly in Kazakhstan, in support of SDGs.